2022
DOI: 10.3390/ijms232415686
|View full text |Cite
|
Sign up to set email alerts
|

A Protective Role of Phenylalanine Ammonia-Lyase from Astragalus membranaceus against Saline-Alkali Stress

Abstract: Phenylalanine ammonia-lyase (PAL, E.C.4.3.1.5) catalyzes the benzene propane metabolism and is the most extensively studied enzyme of the phenylpropanoid pathway. However, the role of PAL genes in Astragalus membranaceus, a non-model plant showing high capability toward abiotic stress, is less studied. Here, we cloned AmPAL and found that it encodes a protein that resides in the cytoplasmic membrane. The mRNA of AmPAL was strongly induced by NaCl or NaHCO3 treatment, especially in the root. Overexpressing AmPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…These findings indicate that some PALs may take part in response to abiotic or biotic stress. Several recent studies have demonstrated this [8,9]. For example, overexpressing of FuPAL1 gene from F. unibracteata enhanced drought tolerance in Arabidopsis [8].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…These findings indicate that some PALs may take part in response to abiotic or biotic stress. Several recent studies have demonstrated this [8,9]. For example, overexpressing of FuPAL1 gene from F. unibracteata enhanced drought tolerance in Arabidopsis [8].…”
Section: Discussionmentioning
confidence: 81%
“…Many studies have shown that the accumulation of phenylpropanoid compounds was correlated with PAL activity [3][4][5]. PALs have been characterized in rice [6], wheat [7], castor [3], Fritillaria unibracteata [8], Astragalus membranaceus [9], and Panax ginseng [10] because of PAL significance for phenylpropanoid biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the observed boost in the content of antioxidant metabolites in treated plants could be related to the higher accumulation of phenylalanine, as shown in Table 4, because of its function and role o as a precursor of numerous metabolites in plant defence systems against environmental stress such as flavonoids, polyphenols, and anthocyanins [57]. Moreover, the responses of phenylalanine and anthocyanins in this study confirm the shifts in the activity of the phenylalanine ammonialyase (PAL) enzyme, especially in OMW-AMF treatment Table 4 The effect of arbuscular mycorrhizal fungus (AMF) and olive mill waste (OMW) on some phenolic acid (mg g −1 DW), flavonoid compound (mg g −1 DW), phenylalanine amino acid (mg g −1 protein), and the activity of phenylalanine amnio lyase (PAL) enzyme (nkatal mg −1 protein) and chalcone synthase (CHS) (nmol mg −1 protein min −1 ) in oat plants 4), which is responsible for catalyzing the deamination of phenylalanine as the foremost and rate-limiting stage of the phenylpropanoid pathway at the regulation point between primary and secondary metabolites [58]. Similarly, Xi et al [4] reported that AMF can maintain the proteins involved in phenylalanine metabolism at a high level under Sb stress and modulate the adverse effects of stress on plant cells.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of anthocyanins in plant vegetative tissues and flowers is affected by internal factors and external environmental factors such as light, temperature, hormones, sugar, etc. [ 24 , 43 ]. WRKY TFs participate in light signaling pathways.…”
Section: Discussionmentioning
confidence: 99%